Metabolomics screening identifies reduced L-carnitine to be associated with progressive emphysema - Conlon, Thomas M.; Bartel, Joerg; Ballweg, Korbinian; Guenter, Stefanie; Prehn, Cornelia; Krumsiek, Jan; Meiners, Silke; Theis, Fabian J.; Adamski, Jerzy; Eickelberg, Oliver; Yildirim, Ali Oender (Clinical Science, 2016)
Chronic obstructive pulmonary disease (COPD) is characterized by chronic bronchitis, small airway remodelling and emphysema. Emphysema is the destruction of alveolar structures, leading to enlarged airspaces and reduced surface area impairing the ability for gaseous exchange. To further understand the pathological mechanisms underlying progressive emphysema, we used MS-based approaches to quantify the lung, bronchoalveolar lavage fluid (BALF) and serum metabolome during emphysema progression in the established murine porcine pancreatic elastase (PPE) model on days 28, 56 and 161, compared with PBS controls. Partial least squares (PLS) analysis revealed greater changes in the metabolome of lung followed by BALF rather than serum during emphysema progression. Furthermore, we demonstrate for the first time that emphysema progression is associated with a reduction in lung-specific L-carnitine, a metabolite critical for transporting long-chain fatty acids into the mitochondria for their subsequent β-oxidation. In vitro, stimulation of the alveolar epithelial type II (ATII)-like LA4 cell line with L-carnitine diminished apoptosis induced by both PPE and H2O2. Moreover, PPE-treated mice demonstrated impaired lung function compared with PBS-treated controls (lung compliance; 0.067 ± 0.008 ml/cmH20 compared with 0.035 ± 0.005 ml/cmH20, P<0.0001), which improved following supplementation with L-carnitine (0.051 ± 0.006, P<0.01) and was associated with a reduction in apoptosis. In summary, our results provide a new insight into the role of L-carnitine and, importantly, suggest therapeutic avenues for COPD.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Biomarkers; Chronic obstructive pulmonary disease (COPD); Metabolome; Ppoptosis